1998
DOI: 10.2343/geochemj.32.33
|View full text |Cite
|
Sign up to set email alerts
|

Change in D/H ratio, water content and color during dehydration of hornblende.

Abstract: The hydrogen isotopic composition of hornblende in volcanic rocks has potential to indicate processes such as degassing of a magma reservoir, as well as the origin of magmatic water. However, during eruption and high-temperature interaction with air, the isotope composition of hornblende can be altered. In order to establish criteria to select natural hornblende that preserves magmatic hydrogen isotopic ratios, hydrogen isotopic composition (SD), water contents, and colors of hornblendes were measured. A serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In the Hokkaido measurements, a natural amphibole crystal containing 1.66 wt % H 2 O was used as a calibration standard, as described by Miyagi et al . []. At Carnegie Institution on the NanoSIMS, three different silicate glasses containing 0.17, 1.00, and 1.62 wt % H 2 O were used to develop a calibration against the measured mass ratios of 17 OH/ 28 Si [ Hauri et al ., ; Saal et al ., ].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In the Hokkaido measurements, a natural amphibole crystal containing 1.66 wt % H 2 O was used as a calibration standard, as described by Miyagi et al . []. At Carnegie Institution on the NanoSIMS, three different silicate glasses containing 0.17, 1.00, and 1.62 wt % H 2 O were used to develop a calibration against the measured mass ratios of 17 OH/ 28 Si [ Hauri et al ., ; Saal et al ., ].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In addition, oxidation-reduction processes of minerals are considered to be related to dehydration processes (Skogby and Rossman 1989). Miyagi et al (1998) showed a good correlation between water contents and a* (reddishness) values of hornblende and concluded that ferrous to ferric oxidation upon dehydration was the origin of the reddish color change of hornblende. Iron is also a major transition element of rhyolitic glasses in pumices.…”
Section: Introductionmentioning
confidence: 94%
“…This process requires secondary exchange of hydrogen isotopes between amphiboles and the methane-dominated fluid and/or water derived from such methane. Such secondary exchange between earlier crystallized minerals and late-stage fluids that may even be internally generated has previously been suggested to account for a large range in ␦D values of amphiboles in a number of volcanic rocks (e.g., Miyagi et al, 1998;Miyagi and Matsubaya, 2003). It is also worth noting that a number of authors suggested that the formation of hydrocarbons could be related to late-or postmagmatic alteration of Fe-rich minerals resulting in the production of H 2 (e.g., Salvi and Williams-Jones, 1997;Potter et al, 1998).…”
mentioning
confidence: 96%